A comparison of thermal comfort data of an integrated thermal comfort meter, meters measuring individual parameters, and human subjects: an outdoor field experiment - Ibrahim, Md. Najib; Abdul Majid, Noor Hanita (1999)
Thermal comfort meter is an integrated equipment designed for indoors. This study reports the experience of using thermal comfort meter at the outdoors. A comparison was made between individual equipment and the integrated thermal comfort meter. A comparison was also made between objective assessment of the thermal comfort meter and subjective assessment of human subjects.